INOVASI PELAYANAN (NASI UDUK INHIL) SEDERHANA SEKALI URUS ADMINISTRASI KEPENDUDUKAN INDRAGIRI HILIR - Budi Setiawan Febriansyah; Mimin Sundari Nasution (Cross-border, 2022)
The Department of Population and Civil Registration of Indragiri Hilir Regency provides innovations in technology-based population document creation services in the era of globalization to meet the needs of the community in dealing, the innovations provided in the service sector are based on the increasing needs of the community in the hope of providing more transparent services, accountable and accessible to all levels of society in Indragiri Hilir Regency. Nasi uduk inhil innovation will provide convenience in getting services, by utilizing digitalization through a transition process from previous innovations. The purpose of this study was to determine the innovation of nasi uduk service in Indragiri Hilir Regency, as well as the challenges in the implementation process. This study uses a qualitative research method with a descriptive approach. The result of this research is that the innovation of Nasi Uduk Inhil service is still not running optimally because the service process has not worked effectively and efficiently as expected, and has inhibiting factors in terms of the lack of education for Nasi Uduk Inhil and network disturbances.